Characterization, Simulation, and Test Method for Image Artifacts Due to Phase Drift of the Saw Filter in the Magnetic Resonance Receiver - (:unkn) unknown (My University, 2023)
The receiver for a Magnetic Resonance (MR) scanner is responsible for capturing the precise frequency and phase of extremely low-power RF signals emanating from the human body; and consequentially must minimize unexpected phase drift in the received signal. One well-known source for temperature-dependent phase drift in RF electronics is the Surface Acoustic Wave (SAW) filter. In this work, the phase drift due to temperature changes in the SAW filter of an MR receiver was evaluated for its potential effects on image quality using several image quality metrics. A lab bench method was developed to playback MR images using typical lab-equipment and an MR receiver while heating the receiver’s SAW filter. Simulations based on the SAW filter’s properties were developed to see if the experimental image data agreed with theoretical predictions. The data were used to determine a recommended specification of 1° phase drift per received signal (or N° of phase drift over the course of a scan containing N phase-encoding steps). These two methods for evaluating phase drift in the MR signal showed 0.1% agreement in image error using a Spin Echo pulse sequence and a 1.7% agreement in image error using a Fast Spin Echo pulse sequence. Defining electrical and thermal requirements on the SAW filter will open the door for design improvements that can ensure a reliable, stable receive path regardless of the receiver’s thermal environment.
Keywords: Image Quality; MRI; SAW Filter